Estrategia de comunicación digital para Lima en tu bolsillo - Oviedo Solís, Fernanda Mariana (2024)
In a post-pandemic context, many social media accounts began to promote various places in Lima, motivating users to visit them. With all these accounts, Lima en tu bolsillo was born with a proposal to differentiate itself from the others by sharing activities (called “planes” by the brand) according to the users’ available budget for the day; both on Instagram and TikTok. These plans are divided into four categories: misio, ajustado, tranqui and pudiente; and they are aimed at a young audience from the AB NSE (Spanish acronym for socio-economic levels). Given this, the main objective of this paper is to increase the brand awareness to a larger audience than the one already obtained, through actions such as a content strategy, digital advertising, collaboration with key accounts, influencer marketing strategy and a brand perception survey.